Road Safety Assessment Tool (RSAT) for road design / Raja Nurulhaiza Raja Nhari and Sitti Asmah Hassan - Raja Nhari, Raja Nurulhaiza; Hassan, Sitti Asmah (2021)
In Malaysia, there is an absence of standard guidelines to determine the level of safety at the design stage road project. This research aims to evaluate the road safety assessment tool for road design projects by determining the level of safety for road design projects. The survey was distributed to 250 respondents to get the respondents' opinion about the road safety issue. There were five (5) elements in the survey namely: cross-section, vertical and horizontal alignment, signage, pavement marking and delineation; and street lighting. A statistical approach was then used to obtain the multiplying factor of the elements asked in the survey. Based on this, the Road Safety Assessment Tool (RSAT) was then developed to check the level of safety for road design projects based on the multiplying factor and index ratio resulting from the analysis. The RSAT give recommendations based on the Level of Safety where a result score of more than 80% reflects that the road design project has passed the minimum safety level and can proceed with the amendment. However, a score of less than 80% means that the project is recommended to be redesigned due to noncompliance with JKR Standard. The results of the study indicate that the use of RSAT to determine the level of safety for road design projects is valid and comparable with the recommendation in the Road Safety Audit Report. It can be concluded that RSAT can be one of the complementary tools to assist in the implementation of Road Safety Audit. This study could provide a model for local agencies nationwide to implement road safety audit recommendations more effectively.